PENGEMBANGAN BAHAN AJAR MATA KULIAH PEMBELAJARAN BILINGUAL BERBASIS ESP BERORIENTASI PJBL UNTUK MAHASISWA PGSD UNIMED - Simanjuntak, Eva Betty; Simbolon, Naeklan; Simanihuruk, Lidia; Sirait, Albert Pauli (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
This aim of this research is to develop teaching material of Billingual Learning Course for PGSD Student of Unimed. This research uses the dick and carrey model on develop the teaching material. The results of this research are: (1) Description of the needs for Bilingual learning materials, (2) Skills needed by students in communicating using English in teaching in elementary schools, (3) PJBL-based Bilingual Learning materials and (4) test results data/expert validation namely; English teaching experts gave a score of 36 with an average score for each questionnaire item = 3.6 and teaching materials experts gave a score of 39 with an average score for each questionnaire item = 3.9. Therefore, it can be concluded that the teaching materials of Bilingual Learning using the PJBL model have fulfilled the theoretical aspects of curriculum development and teaching materials development.